Two Pairs of Drosophila Central Brain Neurons Mediate Larval Navigational Strategies Based on Temporal Light Information Processing - Humberg, Tim-Henning; Sprecher, Simon G. (Frontiers in Behavioral Neuroscience, 2018)
Some animals are attracted by sun light, others are highly repulsed by it. Especially for slowly moving animals, such as Drosophila larvae, direct sunlight may be perceived as noxious stimulus as it increases the risk of desiccation, DNA-damaging by UV-light and exposure to predators. For several reasons, model organisms like Drosophila larvae are well-suited for investigating how light cues are translated into an appropriate behavioral output. First, many of the genetic tools, which were created for use in adult fruit flies, work also in larvae. Second, the lower number of cells in Drosophila larvae compared to adults makes this system adequate for reconstructing neural circuits. Third, the relatively simple behavioral repertoire of larvae facilitates the study of basic functions like navigation with regards to light. Larvae navigate robustly away from a light source by the use of several sophisticated behavioral strategies which are based on temporal or spatial information processing. Two central brain neurons, the NP394-neurons, are highly important for larval light avoidance. It was even reported that these cells seem to play a functional role in a putative larval light preference switch right before pupation. However, the exact function of the NP394-neurons in light navigation remains unknown. We here show that the functional role of NP394-neurons in larval light navigation is restricted to behaviors based on temporal information processing, but not for spatial navigation.